High-energy silane polyphosphate hybridized hydromagnesite-based composite powder as well as preparation method and application thereof

Through the preparation of high-energy polyphosphate silane hybrid water magnesite composite powder, the problems of single function, excessive surface polarity, low thermal stability and poor carbonization performance of natural water magnesite powder are solved, and the multifunctionality and application expansion of the composite powder are achieved.

CN119798780APending Publication Date: 2025-04-11JIANGXI GUANGYUAN CHEM +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411997244.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing natural water magnesite powder has single function, excessive surface polarity, low thermal stability and poor carbon-forming performance.

Method used

High-energy polyphosphate silane hybrid water magnesite composite powder is used to form a multi-layer adhesive functional layer to improve the surface performance and functionality of the powder by chemical grafting and physical mixing of high-energy polyphosphate and silane dilution with water magnesite powder.

Benefits of technology

It significantly improves the flame retardant, smoke suppression, rapid carbonization, physical barrier and processing fluidity of composite powders, and improves the functionality and application range of natural water magnesite powders.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798780A_ABST
    Figure CN119798780A_ABST
Patent Text Reader

Abstract

The invention provides high-energy polyphosphoric acid silane hybridized hydromagnesite-based composite powder as well as a preparation method and application thereof, and belongs to the technical field of preparation of green functional materials. High-energy polyphosphoric acid mixed silane is adopted as a surface bonding layer to coat the surface of natural hydromagnesite, a good physical barrier layer is formed, the high-energy polyphosphoric acid mixed silane is grafted to internal natural hydromagnesite powder particles in a chemical bonding mode, the chemical structure is stable, stripping and falling are not prone to occurring in the machining process, and the service life of the natural hydromagnesite powder particles is prolonged. The silane functional bonding layer fully improves the defects of single function, single component and low efficiency of the traditional modifier, and also greatly improves the flame retardant and smoke suppression characteristics of the composite powder. The technical problems that in the prior art, natural mineral powder is single in function, too large in surface polarity, low in thermal stability and poor in char forming performance are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of green functional material preparation, and in particular to a high-energy polyphosphate silane hybrid hydromagnesite-based composite powder and a preparation method and application thereof. Background Art

[0002] At present, many natural biomass materials are mostly used in the fields of environment, soil, agriculture, etc., with low added value and extensive application, and are rarely used in the field of functional powder preparation with higher added value. With the large-scale application of natural products and the demand for enhanced functionality, they have become cost-controllable through large-scale industrial production and can meet the wide application of the industry. More importantly, natural biomass materials have inherent advantages in green environmental protection, and have good environmental degradability and good environmental adaptability in the subsequent failure process, forming a virtuous circle. Among them, adenosine phosphate, as a high-energy phosphate compound, exists in large quantities in animals and plants. It has multiple high-energy phosphate bonds in its chemical structure, has a high phosphoryl transfer potential, and appears as a white powder, is non-toxic, tasteless, and easily soluble in water. It is a good class of high-energy biomass polyphosphate functional compounds.

[0003] For a long time, a large number of natural hydromagnesite mines have been discovered in Liaoning, Qinghai, Anhui and other places. After simple grinding, this type of powder is sold in an extensive manner. It has a single function and low price, low added value and narrow application. After simple physical crushing, although its particle size has decreased to a certain extent, there are a large number of hydroxyl groups on the surface, which is easy to absorb moisture and even agglomerate during use, which seriously limits its use field and brings inconvenience to storage. Its surface properties need to be changed urgently. Organic-inorganic co-hybridization is one of the efficient measures to improve the comprehensive performance of composite powders. At present, the measures used to change natural hydromagnesite are mainly concentrated on the surface modification of traditional silane. Although it can reduce the surface polarity of natural hydromagnesite powder to a certain extent, its functionality is significantly lacking. Sometimes, traditional silane even supports combustion, making it difficult to effectively play an internal and external synergistic role. More importantly, most surface modifiers are basically based on complicated chemical synthesis. A large amount of organic reagents are consumed during the production and preparation process. Most organic reagents cannot adapt well to the environment, which puts great pressure on environmental protection and is not conducive to the development of a low-carbon economy. Therefore, the proportion of natural products in its surface organic layer needs to be improved urgently.

[0004] In order to meet the needs of green, environmentally friendly and multifunctional natural functional powders, the use of a variety of high-energy natural products for organic reconstruction and combination can significantly improve the green and low-carbon characteristics of composite powders. In addition to using natural stone mineral powders to replace chemical powders to improve their low-carbon and environmentally friendly characteristics, the composition of green functional molecules in the external functional layer also needs to be improved. At this stage, there are few application directions for using high-energy biomass products to enhance the functions of natural stone mineral powders. Summary of the invention

[0005] The purpose of the present invention is to provide a high-energy polyphosphate silane hybrid hydromagnesite-based composite powder and a preparation method and application thereof, which are used to solve the technical problems in the prior art that natural mineral powders have single functions, excessive surface polarity, low thermal stability and poor carbon-forming performance.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a high-energy polyphosphate silane hybrid hydromagnesite-based composite powder, which is prepared from the following raw materials: high-energy polyphosphoric acid, silane diluent, and hydromagnesite powder;

[0008] The usage ratio of the high-energy polyphosphoric acid and hydromagnesite powder is 0.5-5 mol:10 kg;

[0009] The silane diluent is a mixture of silane, water and alcohol, wherein the volume ratio of water to alcohol is 1-20:1, the concentration of the silane diluent is 0.5-15M; and the molar ratio of silane to high-energy polyphosphoric acid in the silane diluent is 1-10:1.

[0010] Further, the high-energy polyphosphate includes one or more of adenosine monophosphate, adenosine diphosphate and adenosine triphosphate;

[0011] The silane includes one or more of 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-aminoethyl-3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, 3-diethylenetriaminopropylmethyldimethoxysilane and 3-diethylenetriaminopropyltrimethoxysilane;

[0012] The median particle size D of the hydromagnesite powder 50 0.9~3.8μm.

[0013] The present invention provides a method for preparing a high-energy polyphosphate silane hybrid hydromagnesite-based composite powder, comprising the following steps:

[0014] Step 1), mixing high-energy polyphosphoric acid and water to obtain a high-energy polyphosphoric acid solution, and dispersing silane, water and alcohol together to obtain a silane dilution solution;

[0015] Step 2), mixing the high-energy polyphosphoric acid solution and the silane dilution to obtain a mixed solution;

[0016] Step 3), adding the mixed solution to the preheated hydromagnesite powder, continuing to stir, and then sequentially cooling and drying to obtain a high-energy polyphosphate silane hybrid hydromagnesite-based composite powder.

[0017] Further, in step 1), the concentration of the high-energy polyphosphoric acid solution is 1 to 10 M;

[0018] The mixing is carried out under stirring, the stirring temperature is 18-34° C., the stirring time is 0.2-2 h, and the stirring speed is 100-900 rpm.

[0019] Furthermore, in step 1), the dispersion is carried out under stirring, the stirring temperature is 25 to 45° C., the stirring time is 0.2 to 3 h, and the stirring speed is 100 to 1200 rpm.

[0020] Further, in step 2), the mixing is to add the silane dilution to the high-energy polyphosphoric acid solution at a rate of 0.05 to 0.5 mL / s;

[0021] The mixing is carried out under stirring at a temperature of 35 to 65° C. and a speed of 1000 to 2000 r / min. After the addition of the silane dilution is completed, stirring is continued for 0.5 to 1.5 h.

[0022] Furthermore, in step 3), the addition rate of the mixed solution is 1 to 50 mL / min.

[0023] Furthermore, in step 3), the preheating is carried out under stirring, the stirring speed is 1000-6000 r / min, the stirring temperature is 45-75° C., and the stirring time is 0.2-0.8 h.

[0024] Furthermore, in step 3), the stirring temperature is 90-102° C., the stirring time is 0.2-1.5 h, and the stirring rate is 4000-7000 r / min.

[0025] The present invention also provides an application of a high-energy polyphosphate silane hybridized hydromagnesite-based composite powder in the preparation of a degradable masterbatch.

[0026] Beneficial effects of the present invention:

[0027] 1) The present invention provides a high-energy polyphosphate silane hybrid hydromagnesite-based composite powder (PP-s-NB). The present invention adopts high-energy polyphosphate hybrid silane as a surface adhesive layer to coat the surface of natural hydromagnesite, which has significant advantages in shielding surface hydroxyl sites, reducing powder oil absorption value, and effectively controlling processing costs; and has significant advantages in chemical composition: high-energy polyphosphate silane integrates multiple components such as N, P, sugar rings, aromatic rings, etc., and is also grafted on the internal natural hydromagnesite powder particles by chemical bonding. The chemical structure is stable and not easy to peel off during processing. The silane functional adhesive layer fully improves the defects of traditional modifiers with single function, single component, and low efficiency; in addition, there are significant advantages in function. Significant advantages: By introducing high-energy adenosine polyphosphate as a functional adhesive layer, a large number of multi-N heterocycles, five-membered sugar rings and high-energy polyphosphate binding sites are introduced into the functional adhesive layer, and a multi-level adhesive functional layer of ammonium phosphate is formed with aminosilane, which can greatly improve the flame retardancy and smoke suppression properties of the composite powder. It quickly cross-links into carbon during the combustion process and can synergize with the internal natural hydromagnesite. In a similar temperature range, the expansion flame retardant effect of the external silane phosphate and the non-flammable gas released by the dehydration of the internal inorganic mineral powder are superimposed on each other to form a better physical barrier layer. This type of composite powder has great advantages in rapid carbonization, physical barrier, promoting carbon layer crystallization, synergistic smoke suppression, and enhancing processing fluidity.

[0028] 2) The present invention constructs a high-energy polyphosphate silane hybrid hydromagnesite-based composite powder (PP-s-NB) by combining physical mixing and chemical grafting, so that each component can form a stable functional bonding layer on the natural hydromagnesite powder in a chemically bonded manner, and the preparation process is simple and easy, with a high yield, and is suitable for industrial production. The obtained high-energy polyphosphate silane hybrid hydromagnesite-based composite powder (PP-s-NB) is a white powder, which is friendly to the coloring of the final product, and can effectively expand the application scope of biofunctional molecules in natural mineral powders and enhance their efficiency, fully utilize the advantages of biofunctional molecules in chemical structure to achieve cross-border applications, and realize multiple organic fusions of biofunctional molecules and natural inorganic mineral powders.

[0029] 3) The raw materials used in the present invention are all from nature, mainly plant extracts and natural stone mineral powder, which have significant advantages in green, low-carbon and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of the preparation principle of high-energy polyphosphate silane hybrid hydromagnesite-based composite powder;

[0031] Figure 2 This is a SEM image of the high-energy polyphosphate silane hybrid hydromagnesite-based composite powder prepared in Example 1;

[0032] Figure 3 This is a particle size distribution diagram of the high-energy polyphosphate silane hybrid hydromagnesite-based composite powder prepared in Example 1. DETAILED DESCRIPTION

[0033] The present invention provides a high-energy polyphosphate silane hybrid hydromagnesite-based composite powder, which is prepared from the following raw materials: high-energy polyphosphoric acid, silane diluent, and hydromagnesite powder;

[0034] The usage ratio of the high-energy polyphosphoric acid and hydromagnesite powder is 0.5-5 mol:10 kg;

[0035] The silane diluent is a mixture of silane, water and alcohol, wherein the volume ratio of water to alcohol is 1-20:1, the concentration of the silane diluent is 0.5-15M; and the molar ratio of silane to high-energy polyphosphoric acid in the silane diluent is 1-10:1.

[0036] In the present invention, the usage ratio of the high-energy polyphosphoric acid to the hydromagnesite powder is preferably 1-4 mol:10 kg, and more preferably 3 mol:10 kg.

[0037] In the present invention, the volume ratio of water to alcohol in the silane dilution is preferably 5 to 15:1, more preferably 10:1;

[0038] The concentration of the silane dilution solution is preferably 1-13M, more preferably 3-10M, and even more preferably 7M.

[0039] In the present invention, the molar ratio of silane to high-energy polyphosphoric acid is preferably 2 to 8:1, more preferably 4 to 7:1, and even more preferably 6:1.

[0040] In the present invention, the high-energy polyphosphate includes one or more of adenosine monophosphate, adenosine diphosphate and adenosine triphosphate, preferably adenosine monophosphate, adenosine diphosphate or adenosine triphosphate, more preferably adenosine monophosphate or adenosine diphosphate, and more preferably adenosine monophosphate;

[0041] The silane includes one or more of 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-aminoethyl-3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, 3-diethylenetriaminopropylmethyldimethoxysilane and 3-diethylenetriaminopropyltrimethoxysilane, preferably It is one or more of 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropylmethyldiethoxysilane and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, more preferably one or more of 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane and 3-aminopropyltriethoxysilane, more preferably 3-aminopropylmethyldimethoxysilane;

[0042] The median particle size D of the hydromagnesite powder 50 The thickness is 0.9 to 3.8 μm, preferably 1.2 to 3.5 μm, more preferably 1.8 to 3 μm, and still more preferably 2.5 μm.

[0043] In the present invention, the hydromagnesite powder is obtained by grinding the natural hydromagnesite mineral powder in layers multiple times by physical method.

[0044] The present invention provides a method for preparing a high-energy polyphosphate silane hybrid hydromagnesite-based composite powder, comprising the following steps:

[0045] Step 1), mixing high-energy polyphosphoric acid and water to obtain a high-energy polyphosphoric acid solution, and dispersing silane, water and alcohol together to obtain a silane dilution solution;

[0046] Step 2), mixing the high-energy polyphosphoric acid solution and the silane dilution to obtain a mixed solution;

[0047] Step 3), adding the mixed solution to the preheated hydromagnesite powder, continuing to stir, and then sequentially cooling and drying to obtain a high-energy polyphosphate silane hybrid hydromagnesite-based composite powder.

[0048] In the present invention, in step 1), the concentration of the high-energy polyphosphoric acid solution is 1 to 10 M, preferably 3 to 7 M, and more preferably 5 M;

[0049] The mixing is carried out under stirring at a temperature of 18 to 34°C, preferably 20 to 30°C, and more preferably 25°C;

[0050] The stirring time is 0.2 to 2 hours, preferably 0.5 to 1.5 hours, and more preferably 1 hour;

[0051] The stirring rotation speed is 100 to 900 rpm, preferably 200 to 800 rpm, more preferably 400 to 600 rpm, and even more preferably 500 rpm.

[0052] In the present invention, in step 1), the dispersion is carried out under stirring, and the stirring temperature is 25 to 45°C, preferably 28 to 40°C, more preferably 32 to 38°C, and more preferably 35°C;

[0053] The stirring time is 0.2 to 3 hours, preferably 0.5 to 2.5 hours, more preferably 1 to 2 hours, and more preferably 1.5 hours;

[0054] The stirring rotation speed is 100 to 1200 rpm, preferably 300 to 1000 rpm, more preferably 500 to 800 rpm, and even more preferably 650 rpm.

[0055] In the present invention, in step 2), the mixing is to add the silane dilution to the high-energy polyphosphoric acid solution at a rate of 0.05 to 0.5 mL / s, preferably 0.1 to 0.4 mL / s, and more preferably 0.3 mL / s;

[0056] The mixing is carried out under stirring at a temperature of 35 to 65° C., preferably 40 to 60° C., and more preferably 50° C.;

[0057] The stirring speed is 1000-2000 r / min, preferably 1200-1800 r / min, and more preferably 1500 r / min;

[0058] After the addition of the silane dilution is completed, stirring is continued for 0.5 to 1.5 h, preferably 0.8 to 1.2 h, and more preferably 1 h.

[0059] In the present invention, in step 3), the addition rate of the mixed solution is 1 to 50 mL / min, preferably 10 to 40 mL / min, more preferably 20 to 30 mL / min, and more preferably 25 mL / min.

[0060] In the present invention, in step 3), the preheating is carried out under stirring, and the stirring speed is 1000-6000r / min, preferably 2000-5000r / min, more preferably 3000-4000r / min, and more preferably 3500r / min;

[0061] The stirring temperature is 45 to 75°C, preferably 50 to 70°C, and more preferably 60°C;

[0062] The stirring time is 0.2 to 0.8 h, preferably 0.5 h.

[0063] In the present invention, in step 3), the mixed solution is preferably added to the high-speed stirred hydromagnesite powder in the form of a spray.

[0064] In the present invention, in step 3), the stirring temperature is 90 to 102°C, preferably 95 to 100°C, and more preferably 98°C;

[0065] The stirring time is 0.2 to 1.5 h, preferably 0.5 to 1 h, and more preferably 0.8 h;

[0066] The stirring rate is 4000-7000 r / min, preferably 5000-6000 r / min, and more preferably 5500 r / min.

[0067] In the present invention, the cooling is to allow the powder to stand in a high-speed mixer for 0.5 to 2.0 hours, preferably 1 to 1.5 hours, and more preferably 1.3 hours after stopping stirring.

[0068] In the present invention, the separation after standing is preferably carried out by separating the cooled powder by a cyclone separator.

[0069] In the present invention, the median particle size of the powder obtained after separation is 1.0 to 4.0 μm.

[0070] In the present invention, the inlet velocity of the cyclone separator is 1-20 m / s, preferably 10 m / s, the separation time is 1-8 min, preferably 5 min, and the number of separations is 1-3 times, preferably 2 times.

[0071] In the present invention, the drying is preferably flash drying, the drying power is 600-1600W, preferably 800-1200W, more preferably 1000W, the drying temperature is 95-105°C, preferably 100°C, the drying time is 1-8min, preferably 2-6min, more preferably 4min.

[0072] The present invention also provides an application of a high-energy polyphosphate silane hybridized hydromagnesite-based composite powder in the preparation of a degradable masterbatch.

[0073] In the present invention, the base material of the degradable masterbatch is preferably a polybutylene adipate-terephthalate / polylactic acid composite material (PBAT / PLA).

[0074] In the present invention, the preparation method of the degradable masterbatch comprises the following steps: mixing polybutylene adipate-terephthalate, polylactic acid, thermoplastic starch and high-energy polyphosphate silane hybrid hydromagnesite-based composite powder, extruding in a twin-screw extruder, air-cooling and drum pelletizing to obtain PBAT / PLA composite masterbatch; pressing the obtained PBAT / PLA composite masterbatch in a flat vulcanizer to prepare a test specimen, that is, obtaining a biodegradable PBAT / PLA composite masterbatch.

[0075] In the present invention, the addition ratio of the polybutylene adipate-terephthalate, polylactic acid, thermoplastic starch and high-energy polyphosphate silane hybrid hydromagnesite-based composite powder is 60:35:10:8-20, preferably 60:35:10:10-18, and further preferably 60:35:10:15.

[0076] In the present invention, the polybutylene adipate-terephthalate is preferably one or more of THJS-8801, C1200, THJS-7801, THJS-6801, BFX103, BFX3091, KM801T, KM801, KM801T, BFX3091, KHB21, ECO-A05, HF101, MG-901S and L604F, and further preferably one or more of THJS-8801, C1200, THJS-7801, THJS-6801, BFX103 and BFX3091;

[0077] The PLA is preferably PLA2300D, 4032D, 6801, 6302D, 4060D, 2002D, 3251D, 6204D, 6260D, 2003D, 6252D, 3260HP, 4044D, 6060D, 6362D, 6202D, 6752D, 6201D, 7032D, 3001D, 8052D, 3251D, 3001D, 7 One or more of 001D, 6100D, 6202D, 201, 6400D, 3020, 3251D and FY804, and further preferably one or more of PLA2300D, 4032D, 6801, 6302D, 4060D, 2002D, 3251D, 6204D, 6260D, 2003D, 6252D, 3260HP, 4044D and 6060D.

[0078] When the dosage ratio of high-energy polyphosphoric acid to natural hydromagnesite ore powder is lower than 0.5 mol: 10 kg, the addition amount of high-energy polyphosphoric acid is too low, and it is difficult to form a good functional bonding layer with silane on the surface of natural hydromagnesite mineral powder, and it is also difficult to form a good modification and shielding effect on natural hydromagnesite mineral powder. The modification effect is very limited, which is not conducive to the functional enhancement and internal and external synergy of the composite powder; on the other hand, when the dosage ratio of high-energy polyphosphoric acid to natural hydromagnesite ore powder is higher than 5 mol: 10 kg, it may cause excessive accumulation of high-energy polyphosphoric acid on the surface, and the bonding layer formed with silane is too thick. Excessive amount may even wrap multiple natural hydromagnesite ore powder particles together, resulting in passive wrapping and aggregation, and may even be peeled off during processing, and the fluidity is reduced, which is not conducive to the improvement of the mechanical properties, dispersion properties and internal and external synergy of the masterbatch.

[0079] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0080] Example 1

[0081] 1 mol of adenosine monophosphate was dissolved in deionized water, and stirred at 600 rpm for 1 h at 23°C to obtain a 2M adenosine monophosphate solution; 5 mol of 3-aminopropylmethyldimethoxysilane was dispersed in a water-alcohol mixture with a volume ratio of 10:1 and stirred at 1200 r / min for 0.5 h at 30°C to obtain a silane dilution with a concentration of 5M;

[0082] The silane dilution was added to the high-energy polyphosphoric acid mixed solution at a rate of 0.1 mL / s, and the mixture was stirred at a speed of 1500 rpm at 50° C. until the addition was complete and the stirring was continued for 1 hour to obtain a mixed solution;

[0083] 10kg median particle size D 50 =2.0 μm natural hydromagnesite mineral powder is placed in a high-speed mixer and preheated at 55°C at a speed of 3000 r / min for 0.5 h; the mixed solution is added to the hydromagnesite mineral powder in the form of a spray at a rate of 20 mL / min, and then the stirring temperature is raised to 95°C, and the stirring is continued at a speed of 5000 r / min for 0.5 h, and then it is allowed to stand for 1 h to cool; the cooled powder is passed through a cyclone separator, the inlet speed is set to 10 m / s, the separation time is 4 min, the number of separations is 2 times, and after obtaining a composite powder with a median particle size of 2.2 μm, it is flash dried at a power of 1000 W and a temperature of 100°C for 4 min to obtain a high-energy polyphosphate silane hybrid hydromagnesite-based composite powder.

[0084] The microscopic morphology of the high-energy polyphosphate silane hybrid hydromagnesite-based composite powder prepared in this example was characterized by scanning electron microscopy.

[0085] Example 2

[0086] 1 mol of adenosine diphosphate was dissolved in deionized water, and stirred at 600 rpm for 0.2 h at 23°C to obtain a 1 M adenosine diphosphate solution; 5 mol of 3-aminopropyltrimethoxysilane was dispersed in a water-alcohol mixture with a volume ratio of 1:1 to obtain a silane dilution with a concentration of 0.5 M;

[0087] The silane dilution was added to the high-energy polyphosphoric acid mixed solution at a rate of 0.05 mL / s, and the mixture was stirred at a speed of 2000 rpm at 35° C., and the stirring was continued for 1.5 h after the addition was complete to obtain a mixed solution;

[0088] 10kg median particle size D 50 =2.0 μm natural hydromagnesite mineral powder is placed in a high-speed mixer and preheated at 75°C at a speed of 1000 r / min for 0.2 h; the mixed solution is added to the hydromagnesite mineral powder in the form of a spray at a rate of 1 mL / min, and then the stirring temperature is raised to 90°C, and the stirring is continued at a speed of 4000 r / min for 1.5 h, and then it is allowed to stand for 0.5 h to cool; the cooled powder is passed through a cyclone separator, the inlet speed is set to 1 m / s, the separation time is 8 min, the number of separations is 3 times, and after obtaining a composite powder with a median particle size of 2.2 μm, it is flash dried at a power of 600 W and a temperature of 95°C for 8 min to obtain a high-energy polyphosphate silane hybrid hydromagnesite-based composite powder.

[0089] Example 3

[0090] 1 mol of 5'-adenosine triphosphate was dissolved in deionized water, and stirred at 100 rpm for 2.0 h at 25°C to obtain a 5'-adenosine triphosphate solution with a concentration of 10 M; 10 mol of N-2-aminoethyl-3-aminopropyltriethoxysilane was stirred at 800 r / min for 1 h at 45°C, and dispersed in a water-alcohol mixture with a volume ratio of 20:1 to obtain a silane dilution with a concentration of 15 M;

[0091] The silane dilution was added to the high-energy polyphosphoric acid mixed solution at a rate of 0.5 mL / s, and the mixture was stirred at a speed of 1000 rpm at 65° C. and continued to be stirred for 0.5 h after the addition was complete to obtain a mixed solution;

[0092] 10kg median particle size D 50=2.0μm natural hydromagnesite mineral powder is placed in a high-speed mixer and preheated at 45°C at a speed of 6000r / min for 0.8h; the mixed solution is added to the hydromagnesite mineral powder in the form of a spray at a rate of 50mL / min, and then the stirring temperature is raised to 102°C, and the stirring is continued at a speed of 7000r / min for 0.2h, and then it is allowed to stand for 2.0h to cool; the cooled powder is passed through a cyclone separator, and the inlet speed is set to 20m / s, the separation time is 1min, and the number of separations is 1 time. After obtaining a composite powder with a median particle size of 2.2μm, it is flash dried at a power of 1600W and a temperature of 105°C for 1min to obtain a high-energy polyphosphate silane hybrid hydromagnesite-based composite powder.

[0093] Comparative Example 1

[0094] Different from Example 1, in this comparative example, 1 mol of adenosine monophosphate was dissolved in deionized water to obtain an adenosine monophosphate solution with a concentration of 2 M.

[0095] Comparative Example 2

[0096] Different from Example 1, in this comparative example, 6 mol of adenosine monophosphate was dissolved in deionized water to obtain an adenosine monophosphate solution with a concentration of 2 M.

[0097] Comparative Example 3

[0098] Different from Example 1, in this comparative example, only the median particle size D 50 =2.0μm natural hydromagnesite powder.

[0099] The oil absorption value and contact angle and other properties of the high-energy polyphosphate silane hybrid hydromagnesite-based composite powders prepared in Examples 1 to 3, the high-energy polyphosphate silane hybrid hydromagnesite-based composite powders in Comparative Examples 1 to 2, and the natural hydromagnesite powder in Comparative Example 3 were tested. Table 1 shows the test results of the powder properties prepared in Examples 1 to 3 and Comparative Examples 1 to 3.

[0100] The test method is as follows:

[0101] Specific surface area: The specific surface area was tested using BET surface area meter.

[0102] Oil absorption value: tested in accordance with DB / T5211.15-2014 standard.

[0103] Table 1 Performance test results of powders prepared in Examples 1 to 3 and Comparative Examples 1 to 3

[0104] Sample <![CDATA[Specific surface area (m 2 / g)]]> Oil absorption value (mL / 100g) Example 1 20.443 24 Example 2 19.643 26 Example 3 20.331 25 Comparative Example 1 18.331 35 Comparative Example 2 20.012 28 Comparative Example 3 17.112 38

[0105] From the test results of Examples 1 to 3 and Comparative Example 3 in Table 1, it can be found that by introducing high-energy polyphosphoric acid derivatives and silane to form a functional adhesive layer attached to the surface of natural hydromagnesite ore powder, multi-level and multi-component modification of natural hydromagnesite powder can be achieved. In terms of specific surface area, the specific surface area of ​​the obtained composite powder is significantly increased compared with the unmodified natural hydromagnesite mineral powder. This may be because the high-energy polyphosphoric acid silane adhesive layer on the surface can significantly shield the hydroxyl groups and various high-polar groups of the natural hydromagnesite powder, which can significantly improve the agglomeration effect, and thus its specific surface area is increased to a certain extent, and the appropriate addition amount can keep the specific surface area at a high state; in terms of oil absorption value, when the proportion of high-energy polyphosphoric acid silane added on the surface is not appropriate, the oil absorption value of the final composite powder is reduced to a limited extent. In contrast, when a suitable amount of high-energy polyphosphate silane is added to modify the natural hydromagnesite powder, the oil absorption value of the composite powder decreases significantly, from the highest value of 38mL / 100g to 24mL / 100g. This may be because high-energy polyphosphate silane can effectively adhere to the surface of natural hydromagnesite to form an effective shielding effect, greatly reducing its oil absorption effect, which has a great promoting effect on dispersion control and cost control in subsequent processing.

[0106] The high-energy polyphosphate silane hybrid hydromagnesite-based composite powders prepared in Examples 1 to 3, the high-energy polyphosphate silane hybrid hydromagnesite-based composite powders in Comparative Examples 1 to 2, and the natural hydromagnesite powder in Comparative Example 3 were used to prepare biodegradable functional masterbatches, and the performance of the obtained biodegradable functional composite substrates was tested. The specific method is as follows:

[0107] First, PBAT, PLA, TPS and PP-s-NB were dried in an oven for 12 h, and the drying temperature was controlled to 80 ° C. 60 parts of PBAT (C1200), 35 parts of PLA (2003D) and 10 parts of TPS were mixed by mass, and then melt blended in a twin-screw extruder, the temperature was controlled at 150 ° C, the main engine speed was 200 r / min, extruded and air-cooled, and then drum pelletized to obtain PBAT / PLA composite masterbatch, and the high-energy polyphosphate silane hybrid hydromagnesite-based composite powder (PP-s-NB, 12 parts) prepared in Examples 1 to 3 and Comparative Examples 1 to 2 after drying and the natural hydromagnesite powder (12 parts) described in Comparative Example 3 were added respectively, and then kneaded at 165 ° C for 5 min, and then subjected to pressing (170 ° C, back pressure 10 MPa), micro injection molding (170 ° C, holding temperature 10s, injection pressure 70 MPa) to prepare various test specimens for standby use. Table 2 shows the performance test results of the PBAT / PLA composite materials prepared using the powders obtained in Examples 1 to 3 and Comparative Examples 1 to 3.

[0108] Thermal gravimetric test: nitrogen atmosphere, heating rate 20℃ / min, starting temperature: 30℃, maximum temperature: 800℃.

[0109] Limiting oxygen index: ASTM D2863 test.

[0110] Vertical burning: ASTM D3801-2010.

[0111] Melt index: ISO1133-2011, 180°C, load 2.16kg.

[0112] Tensile strength test: GB / T1040-2006, 23±2℃.

[0113] Table 2 Performance test results of PBAT / PLA composite materials prepared from the powders obtained in Examples 1 to 3 and Comparative Examples 1 to 3

[0114]

[0115] By comparing the data on the carbon residue quality of the PBAT / PLA composite material prepared by the powders described in Examples 1 to 3 and Comparative Example 3, it can be seen that the introduction of a suitable proportion of high-energy polyphosphate silane functional bonding layer and natural hydromagnesite powder in combination can significantly improve the carbon residue quality of the final composite material, with the maximum increase from 5.2% to 15.3%. It can be seen that the external high-energy polyphosphate silane layer and the internal natural hydromagnesite powder have a typical internal and external synergistic effect, which can effectively promote the formation of the carbon layer of the final composite substrate and significantly improve the barrier effect during the combustion process. In terms of macroscopic combustion performance, the LOI value of the composite substrate increased from 21.5% to 28.6% at most, which changed the composite substrate from a combustible material to a flame-retardant material. It can be seen that the combination of the high-energy polyphosphate silane layer and the internal natural hydromagnesite takes into account the advantages of multiple components of organic phosphorus system, inorganic silicon system and inorganic hydroxide, and can significantly improve the flame retardant properties of the composite substrate. At the same time, in the vertical combustion test, the hydromagnesite-based composite powder with a suitable proportion of high-energy polyphosphate silane added can improve the flame retardant properties of the composite substrate in the vertical direction. In contrast, When the powders in proportions of 1 to 3 were added to the PBAT / PLA composite matrix, the vertical combustion levels all decreased to varying degrees, indicating that the internal and external synergistic performance was low or completely non-existent at this time; in terms of processing performance, the introduction of high-energy polyphosphate silane can improve the melt index of the composite material to a certain extent and improve the flow state of the composite material during processing. This may be because the introduction of the composite powder effectively promoted the relative flow and slip of the molecular chains. When the composite powder without effective surface modification was added to the composite matrix, a strong interaction between the powder and the molecular chain may occur, and even agglomeration may occur so that the powder and the molecular chain may be separated in the blending system, resulting in an enhanced entanglement ability between the molecular chains of the polymer matrix in the blending material and a deterioration of its processing fluidity; in the mechanical tensile test process, after the high-energy polyphosphate silane with a suitable proportion was introduced into the natural hydromagnesite powder, the dispersion and compatibility of the composite powder in the polymer matrix could be improved, and the aggregation effect of the natural hydromagnesite powder in the polymer composite matrix could be effectively avoided, so that the tensile resistance of the PBAT / PLA composite matrix was improved, with a maximum increase of 61.6%. In summary, the introduction of high-energy polyphosphate silane functional bonding layer not only has significant advantages in improving powder properties, controlling oil absorption value, and cost control, but also can better strengthen the synergistic effect with the natural hydromagnesite core, forming a reinforced physical barrier layer to resist the impact of air flow, mass flow and heat flow during the combustion process, thereby playing a significant role in flame retardancy and improving the quality and quantity of residual carbon. In addition, in terms of processing fluidity and mechanical properties, due to the improvement of powder properties, its dispersibility and compatibility in the polymer PBAT / PLA matrix are effectively improved.In comparison, Comparative Examples 1 to 2 are inferior to Examples 1 to 3 in terms of charring quality, and are not as effective as Examples 1 to 3 in terms of combustion performance tests. The performance improvements in processing fluidity and tensile strength are also limited. This may be because the external high-energy polyphosphate silane and the internal natural hydromagnesite are difficult to form an effective internal and external synergistic effect, and the various macroscopic properties of the composite substrate are difficult to improve.

[0116] It can be seen from the above embodiments that the present invention provides a high-energy polyphosphate silane hybrid hydromagnesite-based composite powder and a preparation method and application thereof. Figure 1 Schematic diagram of the preparation principle of high-energy polyphosphate silane hybrid hydromagnesite-based composite powder; Figure 2 This is a SEM image of the high-energy polyphosphate silane hybrid hydromagnesite-based composite powder prepared in Example 1; Figure 3 This is a particle size distribution diagram of the high-energy polyphosphate silane hybrid hydromagnesite-based composite powder prepared in Example 1. Figure 3 As shown, there are multiple coated particles on the surface of natural hydromagnesite powder, so that there is a relatively continuous coating layer on its surface, which is effectively attached to the surface of natural hydromagnesite mineral powder to form a hybrid material. The present invention solves the problems of single function, excessive surface polarity, low thermal stability and poor carbonization performance of natural mineral powder in the prior art.

[0117] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-energy polyphosphate silane hybrid hydromagnesite-based composite powder, characterized in that: The method is prepared from the following raw materials: high-energy polyphosphoric acid, silane dilution, and hydromagnesite powder; The usage ratio of the high-energy polyphosphoric acid and hydromagnesite powder is 0.5-5 mol:10 kg; The silane diluent is a mixture of silane, water and alcohol, wherein the volume ratio of water to alcohol is 1-20:1, the concentration of the silane diluent is 0.5-15M; and the molar ratio of silane to high-energy polyphosphoric acid in the silane diluent is 1-10:

1.

2. The high-energy polyphosphate silane hybrid hydromagnesite-based composite powder according to claim 1, characterized in that: The high-energy polyphosphate includes one or more of adenosine monophosphate, adenosine diphosphate and adenosine triphosphate; The silane includes one or more of 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-aminoethyl-3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, 3-diethylenetriaminopropylmethyldimethoxysilane and 3-diethylenetriaminopropyltrimethoxysilane; The median particle size D of the hydromagnesite powder 50 0.9~3.8μm.

3. The method for preparing the high-energy polyphosphate silane hybrid hydromagnesite-based composite powder according to claim 1 or 2, characterized in that: The following steps are involved: Step 1), mixing high-energy polyphosphoric acid and water to obtain a high-energy polyphosphoric acid solution, and dispersing silane, water and alcohol together to obtain a silane dilution solution; Step 2), mixing the high-energy polyphosphoric acid solution and the silane dilution to obtain a mixed solution; Step 3), adding the mixed solution to the preheated hydromagnesite powder, continuing to stir, and then sequentially cooling and drying to obtain a high-energy polyphosphate silane hybrid hydromagnesite-based composite powder.

4. The method for preparing the high-energy polyphosphate silane hybrid hydromagnesite-based composite powder according to claim 3, characterized in that: In step 1), the concentration of the high-energy polyphosphoric acid solution is 1 to 10 M; The mixing is carried out under stirring, the stirring temperature is 18-34° C., the stirring time is 0.2-2 h, and the stirring speed is 100-900 rpm.

5. The method for preparing the high-energy polyphosphate silane hybrid hydromagnesite-based composite powder according to claim 3 or 4, characterized in that: In step 1), the dispersion is carried out under stirring, the stirring temperature is 25 to 45° C., the stirring time is 0.2 to 3 hours, and the stirring speed is 100 to 1200 rpm.

6. The method for preparing the high-energy polyphosphate silane hybrid hydromagnesite-based composite powder according to claim 5, characterized in that: In step 2), the mixing is to add the silane dilution to the high-energy polyphosphoric acid solution at a rate of 0.05 to 0.5 mL / s; The mixing is carried out under stirring at a temperature of 35 to 65° C. and a speed of 1000 to 2000 r / min. After the addition of the silane dilution is completed, stirring is continued for 0.5 to 1.5 h.

7. The method for preparing the high-energy polyphosphate silane hybrid hydromagnesite-based composite powder according to claim 3, 4 or 6, characterized in that: In step 3), the addition rate of the mixed solution is 1 to 50 mL / min.

8. The method for preparing high-energy polyphosphate silane hybrid hydromagnesite-based composite powder according to claim 7, characterized in that: In step 3), the preheating is carried out under stirring, the stirring speed is 1000-6000 r / min, the stirring temperature is 45-75° C., and the stirring time is 0.2-0.8 h.

9. The method for preparing the high-energy polyphosphate silane hybrid hydromagnesite-based composite powder according to claim 3 or 8, characterized in that: In step 3), the stirring temperature is 90-102° C., the stirring time is 0.2-1.5 h, and the stirring rate is 4000-7000 r / min.

10. Use of the high-energy polyphosphate silane hybrid hydromagnesite-based composite powder according to claim 1 or 2 in the preparation of degradable masterbatch.